2021
DOI: 10.3390/w13020197
|View full text |Cite
|
Sign up to set email alerts
|

Study of the Drag Reduction Characteristics of Circular Cylinder with Dimpled Surface

Abstract: To reduce the drag of a cylinder, numerical simulations and experiments for both smooth cylinder and circular cylinder with the dimpled surface are carried out in this paper. The numerical simulation focuses on the variation of pressure coefficient, skin friction coefficient, and vortex shedding strength of the smooth cylinder and the circular cylinder with the dimpled surface. It is found that the dimpled structure can effectively reduce the drag of the cylinder within a specific range of Reynolds number, and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 28 publications
0
12
0
Order By: Relevance
“…But for the surface smoothed cylinder, the maximum C fθ was at about α = 50°. 6,22 As shown in Figure 17, the presence of the grooves caused C fθ to decrease for the location of α < 80°. As a results, the skin friction drag was lower than that of the surface smoothed cylinder, since the skin friction drag is obtained by integrating.…”
Section: Numerical Results and Discussionmentioning
confidence: 87%
See 1 more Smart Citation
“…But for the surface smoothed cylinder, the maximum C fθ was at about α = 50°. 6,22 As shown in Figure 17, the presence of the grooves caused C fθ to decrease for the location of α < 80°. As a results, the skin friction drag was lower than that of the surface smoothed cylinder, since the skin friction drag is obtained by integrating.…”
Section: Numerical Results and Discussionmentioning
confidence: 87%
“…5 These can both delay the flow separation and result in a smaller wake region, causing a lower drag than the smooth cylinders. [6][7][8] The results of wind tunnel tests have shown that such a conductor performs a lower drag by 32% compared with the conventional conductor at Re = 10 5 in the typhoon condition. 2 There has been an equivalent reduction in drag in field trials.…”
Section: Introductionmentioning
confidence: 99%
“…So, the conclusion can be drawn that when the dimpled distance is set reasonably, the recirculation zone of the circular cylinders with the dimpled surface is larger than that of the smooth cylinder, which means that the structure and number of dimple interfere with the wake vortex. Therefore, the formation of the larger vortex leads to a decrease in the vortex shedding frequency, thus the drag is reduced [27]. Furthermore, a close inspection revealed that b of case 2, case 3, and case 4 was slightly larger than that of case 1, which might be due to an increase in the separation angle [28,29].…”
Section: The Velocity Profiles and Recirculation Zonesmentioning
confidence: 94%
“…Moon, O'Connell and Glezer [17] also noted that studies conducted by other authors on dimples showed a lower pressure drop in comparison to other turbulators (such as continuous ribs) whilst significantly improving the thermal performance by a margin of 38%. Several other authors, including Abbas et al [18], Zhong et al [19] and Yan, Yang and Wang [20], have also conducted studies on the drag reduction properties of dimples on golf balls and cylinders, concluding that the addition of dimples has a significant effect on reducing the overall drag observed.…”
Section: Introductionmentioning
confidence: 99%